Application of a human primary epithelial-fibroblast co-culture system to study fibrosis - Richardson, Jaineeta (2017)
Idiopathic Pulmonary Fibrosis (IPF) is a chronic, progressive lung disease which manifests over several years with an unknown aetiology. The current paradigm suggests that reoccurring injury to the lungs results in damage to the alveolar epithelial cells, progressing to the destruction of the alveolar-capillary basement membrane. Although little is known about how the alveolar epithelium is injured, it is thought that repeated epithelial injury releases a wide variety of soluble factors which can initiate a series of events such as migration, differentiation and activation of mesenchymal cells i.e. fibroblasts into myofibroblasts. Myofibroblasts are proliferative, protected from apoptosis and produce extra-cellular matrix (ECM) in IPF. In turn it is likely these mesenchymal cells modify epithelial behaviour, producing a pro-fibrotic environment. Dysregulation of the normal processes in the lung results in abnormal communication between epithelial and mesenchymal cells which prevents resolution of the wound-repair response leading to tissue fibrosis and eventual organ failure.